Feasibility Analysis (Financial) of Pak Sugi's Tofu and Tempeh Business in Belitar Muka Village, Sindang Kelingi Subdistrict, Rejang Lebong Regency - Fira Juli Andini; Herlin Herlin; Yudi Irawan Abi (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2026)
A feasibility study is important to determine whether a business is financially viable. This study aims to analyse the financial feasibility of Pak Sugi's Tofu and Tempe Business in Belitar Muka Village, Sindang Kelingi Subdistrict, Rejang Lebong Regency. The analysis was conducted by calculating the total costs, total revenue, and income, then assessing the feasibility using the R/C Ratio, B/C Ratio, and Break-Even Point (BEP). The data used were primary and secondary data obtained through interviews and documentation. The results showed that the total production costs for tofu were IDR 10,686,760 and for tempeh IDR 10,443,260, with total revenues of IDR 25,399,000 and IDR 24,945,000, respectively. The net income for tofu is IDR 14,712,240 and for tempeh is IDR 14,501,740. The R/C Ratio for tofu is 2.37 and for tempeh is 2.39, the B/C Ratio for tofu is 1.37 and for tempeh is 1.39, while the BEP results show that the business is above the break-even point. Therefore, Mr. Sugi's tofu and tempeh business is deemed viable and has good prospects for future development.